The Symbolic Meaning of Communication in the Baby Bathing Tradition in Kuta Sayeh Village - Naillis Sakda; Al Zuhri (PT Riset Mandiri Nusantara, 2025)
The baby bathing tradition is a cultural heritage that the community of Kuta Sayeh Village, Seunagan District, Nagan Raya Regency, continues to preserve. This tradition expresses gratitude to God for the birth of a child. Its practice involves various symbols and ritual actions believed to bring blessings to the baby. However, understanding the symbolic meanings embedded in this tradition has gradually diminished, turning its implementation into a mere inherited routine devoid of profound interpretation. This study aims to explore, document, and disseminate the symbolic meanings within the communicative processes of the baby bathing tradition in Kuta Sayeh. The theory employed is Ferdinand de Saussure’s semiotics, utilizing a descriptive qualitative approach. Data were collected through interviews and documentation with purposively selected informants. The findings reveal that each symbol in the ritual carries deep philosophical meaning, expressed through prayers or aspirations. For instance, the Qur'an symbolizes life guidance; pure gold, coconut milk, and sweets signify preciousness, politeness, and guarded speech; tepung tawar represents protection and serenity; chicken heart wrapped in eggplant leaves denotes courage and calmness; sticky rice signifies blessings and prosperity; dates represent sweetness of speech; rice and paddy symbolize abundance; a mirror signifies self-awareness; powder, scissors, and a comb symbolize beauty, new beginnings, and neatness; while a split coconut under an umbrella embodies a peaceful soul. Thus, the tradition encompasses social, moral, and spiritual values that are essential to preserve and reintroduce to younger generations as a meaningful part of local cultural identity.